Evaluation of Dry-Wet Transition in PEFC Under Load Changes Based on Laser Spectroscopy Using Fiber-Optic Probe. (3rd July 2019) - Nishida, Kosuke; Nakauchi, Ryoga; Tabata, Yuma; Umekawa, Toyofumi; Kawasaki, Masahiro
Abstract : To avoid the membrane dryout and performance degradation of polymer electrolyte fuel cells (PEFCs) under low-humidity conditions, it is necessary to understand the dynamic water transport within working cells. In this study, we have developed a real-time gas sensing system with a single-ended fiber-optic probe based on tunable diode laser absorption spectroscopy (TDLAS), to measure the water vapor distribution in narrow channels of fuel cells with high accuracy and high temporal resolution. This sensor was used to evaluate the dry-wet transient phenomena in the anode flow channel of a PEFC during low-humidity and load change operations. The technique showed the water vapor concentration in the anode channel has a large temporary drop when the current density increases and the voltage undershoot occurs. We concluded that the TDLAS-based gas sensing technique enables the detection of instantaneous fluctuations of water concentration in the flow channel observed after step changes of current density.